Biotechnology and plant breeding : (Elsevier, 2014)
Includes critical discussion of the newest and most important applications of biotechnology in plant breeding, covering key topics such as biometry applied to molecular analysis of genetic diversity and genetically modified plants. This work goes beyond recombinant DNA technology to bring together key information and references on new biotech tools for cultivar development such as double haploids, molecular markers, and genome-wide selection, among others.